2020
DOI: 10.1021/acs.orglett.0c02211
|View full text |Cite
|
Sign up to set email alerts
|

Pd/Cu-Catalyzed Domino Cyclization/Deborylation of Alkene-Tethered Carbamoyl Chloride and 1,1-Diborylmethane

Abstract: Reported herein is a palladium/copper cooperative-catalyzed dicarbofunctionalization of alkene-tethered carbamoyl chlorides with 1,1-diborylmethane. This cyclization/deborylation cascade strategy allows for the expedient formation of the versatile borylated 3,3-disubstituted oxindole skeleton, allowing for further functionalization via the derivatization of the carbon–boron bond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 57 publications
0
12
0
1
Order By: Relevance
“…of LiO t Bu as the base, it is possible to obtain the borylated 3,3‐disubstituted oxindole skeleton in high yield (Scheme 36). [83] Qu, Chen and co‐workers suggested that the reaction is initiated by the oxidative addition of 69 to Pd(0) to generate the carbamoyl‐palladium species followed by an intramolecular migratory insertion to deliver the cyclic Pd(II) intermediate. Meanwhile, the monoalkyl cuprate is generated in situ by a copper catalyst and 1,1‐diborylmethane in the presence of LiO t Bu.…”
Section: Reactivity Of Borata‐alkene Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…of LiO t Bu as the base, it is possible to obtain the borylated 3,3‐disubstituted oxindole skeleton in high yield (Scheme 36). [83] Qu, Chen and co‐workers suggested that the reaction is initiated by the oxidative addition of 69 to Pd(0) to generate the carbamoyl‐palladium species followed by an intramolecular migratory insertion to deliver the cyclic Pd(II) intermediate. Meanwhile, the monoalkyl cuprate is generated in situ by a copper catalyst and 1,1‐diborylmethane in the presence of LiO t Bu.…”
Section: Reactivity Of Borata‐alkene Compoundsmentioning
confidence: 99%
“…CuCH 2 Bpin system undergoes facile transmetalation with the alkyl‐palladium species that eventually promote the reductive elimination towards the desired product with the regeneration of the Pd(0) species (Scheme 36). [83] …”
Section: Reactivity Of Borata‐alkene Compoundsmentioning
confidence: 99%
“…该类化合物的手性合成传统上依赖 于步骤繁琐的手性辅基策略, 近期张万斌 [2] 和丁奎岭 [3] 课题组分别报道了不对称氢化的策略构建其中一类 α-苄基取代的 γ-内酰胺, Cramer 课题组 [4] 报道了镍催化的 不对称氢胺甲酰策略构建其中一类 α-甲基取代的 γ-内 酰胺, 然而通用的不对称催化策略到目前为止仍然没有 实现. 华东理工大学化学与分子工程学院陈宜峰和曲景 平团队 [5] 致力于烯烃的双官能团化, 在他们课题组发展 的系列镍催化羰基化反应基础上 [6] , 通过新型手性配体 的理性设计, 发展一类全新的手性 Quinim 配体骨架, 从 廉价易得的高烯丙胺衍生的胺酰氯出发, 通过镍催化还 原偶联策略, 成功实现了烯烃不对称胺甲酰基-烷基双 官能团化反应 [7]…”
Section: He Yuliunclassified
“…Based on the model reaction of carbamoyl chloride 68 with diborylmethane in the presence of 5 mol % Pd(PPh 3 ) 4 / 10 mol % of CuCl, and 2.0 equiv. of LiO t Bu as the base, it is possible to obtain the borylated 3,3‐disubstituted oxindole skeleton 69 in high yield (Scheme 33a) [32] . The high temperature required (80 °C) effectively promote this cascade reaction, whereas the yield dropped to 38 % when the reaction was performed at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction has been generalized for a large number of substrates with electron and steric modifications and notably, non‐aromatic‐ring‐tethered carbamoyl chloride 70 can also be successfully applied to this strategy, although the corresponding product 71 is not stable upon various workup procedures. The oxidized hydroxyl‐substituted γ‐lactam 72 can be synthetized in 43 % isolated yield when the reaction mixture was directly treated with NaBO 3 ⋅ 4H 2 O (Scheme 33b) [32] …”
Section: Introductionmentioning
confidence: 99%